Pengaruh Kombinasi Polimer PVP:EC dan HPMC:EC Terhadap Sediaan Transdermal Pada Karakteristik Patch yang Baik : Review - Fuziyanti, Nova (Brawijaya University, 2022)
Transdermal is a drug delivery system that is placed through the surface of the skin to release the active substance in a certain dose into the bloodstream. The main constituent component in the transdermal drug delivery system which has an effect on characteristics is polymer. One of the developments in the transdermal route is the manufacture of patch preparations. Physically, a good patch must be flexible, thin, smooth, homogeneous, have drying shrinkage and low moisture absorption. So the aim of this review article was to determine the effect of polymer combinations on transdermal preparations on good patch characteristics. The method used in this review article is a literature review of various journals published online, with the category of national and international journals. The results obtained 2 primary journals related to polymer combinations to transdermal preparations, namely the combination of PVP: EC and HPMC: EC. The results of the review show that the polymer combination can have an influence on the characteristics of the patch, including the fold resistance test, weight uniformity test, thickness test, drying shrinkage test and moisture absorption test.